Audit Sistem Informasi Menggunakan Framework COBIT 4.1 (Dengan Domain Monitor and Evaluate) Pada PT. Samudera Indonesia Tbk - Gerald Vidisa Jourdano; Alexander Setiawan; Agustinus Noertjahyana (Jurnal Infra, 2018)
PT. Samudera Indonesia Tbk is a company engaged in the field of logistics services throughout the territory of Indonesia and reach the international sphere. The company divides its business portfolio into 4 lines, namely Samudera Shipping (shipping business), Samudera Agencies (agency business), Samudera Logistics (logistics business), and Samudera Terminal (port business) to deliver integrated transportation and logistics services, and one of branch office located in Surabaya which serving in the field of agency.For a large company with high-complexity business processes and assisted with information technology, the company must be able to provide services that match the business objectives to be achieved. Investment on information technology that has been applied, has not provided a firm guarantee for the company. There are other factors to consider, not just focusing on the use of information technology assets, but companies should focus on monitoring, maintaining, managing and ensuring that companies comply with relevant information technology regulations.Therefore, the researchers using domain of Monitor and Evaluate, to measure the maturity level of enterprise information technology based on monitoring, managing process and how far PT. Samudera Indonesia Tbk comply with applicable information technology laws and external requirements.